Analisis Perbandingan Sistem Struktur Gedung Baja Konvensional dan Sistem Struktur Diagrid dengan Konfigurasi Batang Diagonal yang Berbeda - Nugroho, Bima Candra; Andayani, Relly (Universitas Kristen Maranatha, 2024)
Diagrid is known as a grid structure where the exterior structure of the building is diagonal, this is one of the most innovative and adaptable approaches and also evolved into its use for high-rise buildings. Diagrid is formed from diagonally shaped frames that are interconnected by materials which can be steel, concrete or wood. The purpose of this study is to determine the performance of the diagrid building structure and how the optimal diagonal member configuration for the diagrid building is. There are 6 types of buildings to be reviewed, consisting of 1 conventional building type and 5 diagrid building types, namely diagrid type 2L20M with diagonal members slope of 33,94°, diagrid type 4L10M with a diagonal angel of 53,39°, diagrid type 8L5M with a diagonal angel of 69,62°, type 10L4M diagrid with a diagonal angle of 73,45° and 20L2M type diagrid with a diagonal angle of 81,55°. The buildings will be analyzed using the ETABS program and following the SNI regulations in Indonesia. The performance result to be compared include cross-sectional dimensions, total structure weight and base shear, service limit performance and time period. The result analysis show that the diagrid building has better structural performance. The diagrid model with the most optimal performance is the 10L4M type with a diagonal member length of 36,51 meters that extends up to 10 floors with a module height of 35 meters and an angle of 73,45°. Diagrid model with the second-best performance is type 8L5M, then in third place is type 4L10M and in fourth place is type 20L2M. The diagrid building with the lowest performance is the 2L20M type which has no better performance than conventional buildings.